2013
DOI: 10.1142/s1363919613400124
|View full text |Cite
|
Sign up to set email alerts
|

Innovation Tool Adoption and Adaptation in Small Technology-Based Firms

Abstract: In this paper, we present a qualitative, interview-based study of the processes small technology-based firms go through when they adopt tools and adapt them for use. By extracting 59 instances of tool internalisation across five firms, we derived a coding scheme combining existing and emergent forms of tool bricolage. The four types are reconstruction, reinterpretation, evolution, and customisation. We articulate examples of each type. Our findings reinforce the variability of any given tool once enacted in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
0
8
0
3
Order By: Relevance
“…engineers adopt new tools to appear or feel more innovative (Benders and Slomp, ). Moreover, despite the highly‐structured and analytical nature of these tools, their influence is often limited to providing a guiding framework, or heuristic for practice (Hales and Tidd, ; de Waal and Knott, ; Wright et al, ). Knott () supports this analysis and found that users of strategy tools only used them as a source of inspiration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…engineers adopt new tools to appear or feel more innovative (Benders and Slomp, ). Moreover, despite the highly‐structured and analytical nature of these tools, their influence is often limited to providing a guiding framework, or heuristic for practice (Hales and Tidd, ; de Waal and Knott, ; Wright et al, ). Knott () supports this analysis and found that users of strategy tools only used them as a source of inspiration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of course, it is well known that the implementation of any type of new management concept, organizational tool or method entails challenges (e.g. De Waal & Knott, 2013). It is also well known that innovation poses important challenges for large incumbent firms, in particular when it comes to radical innovation (e.g., Tushman & Nadler, 1986;Assink, 2006;Moss Kanter, 2006;O'Connor, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, for them to adopt and internalise tooluse into practice, we know from other kinds of tool, particularly in the context of IT, that the tool designers' intended use may be extensively modified. For instance, the scope for flexibility to which tools could be adopted might range from small, physical customisations through to re-inventing appropriated wholes or parts of tools to meet new needs (De Waal and Knott, 2013). This internalising of tool-use is dependent on a combination of the EP's intention, skill, experience, as well as local affordances and constraints (Norman 1988;Dix 2007;Dourish 2003;Krippendorff 2006;Cruickshank et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%